Novel cerebrotendinous xanthomatosis mutationcauses familial early dementia in Colombia (2015)
ABSTRACT: Cerebrotendinous xanthomatosis is an infrequent cause of dementia. It is an autosomal recessive disorder with clinical and molecular heterogeneity. Objective: To identify the presence of a possible mutation in a Colombian family with several affected siblings and clinical characteristics compatible with cerebrotendinous xanthomatosis associated to early dementia.Materials and methods: We studied a series of cases with longitudinal follow-up and genetic analysis.Results: These individuals had xanthomas, mental retardation, psychiatric disorders, behavioral changes, and multiple domains cognitive impairment with dysexecutive dominance that progressed to early dementia. CYP27A1 gene coding region sequencing revealed a novel mutation (c.1183_1184insT).Conclusion: The mutation found in this family is responsible for the described dementia features. Early identification of familial history with mental retardation, xanthomas and cognitive impairment might prevent the progression to this treatable type of dementia. Even though this mutation lies in the most frequently mutated codon of CYP27A1 gene, it has not been reported previously.